2023
DOI: 10.1002/advs.202205487
|View full text |Cite
|
Sign up to set email alerts
|

Steering Stem Cell Fate within 3D Living Composite Tissues Using Stimuli‐Responsive Cell‐Adhesive Micromaterials

Abstract: Engineered living microtissues such as cellular spheroids and organoids have enormous potential for the study and regeneration of tissues and organs. Microtissues are typically engineered via self‐assembly of adherent cells into cellular spheroids, which are characterized by little to no cell–material interactions. Consequently, 3D microtissue models currently lack structural biomechanical and biochemical control over their internal microenvironment resulting in suboptimal functional performance such as limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 93 publications
2
7
0
Order By: Relevance
“…The different internalization of GO nanoflakes and BTNPs is mainly due to the considerably different dimensions of those nanomaterials (∼9 μm for the GO nanoflakes and ∼60 nm for the BTNPs). Indeed, large nanomaterials, having a dimension comparable to the cell size are hardly internalized, as confirmed by the state-of-the-art. , This was also confirmed at the experimental level: both noncoated and PDA-coated GO nanoflakes remained confined outside the cells (Figure S18, top), while for BNTPs the PGA coating played a role. In fact, noncoated BTNPs largely remained aggregated in clusters outside the cells, with a few ones internalized (Figure S18, bottom).…”
Section: Resultssupporting
confidence: 62%
“…The different internalization of GO nanoflakes and BTNPs is mainly due to the considerably different dimensions of those nanomaterials (∼9 μm for the GO nanoflakes and ∼60 nm for the BTNPs). Indeed, large nanomaterials, having a dimension comparable to the cell size are hardly internalized, as confirmed by the state-of-the-art. , This was also confirmed at the experimental level: both noncoated and PDA-coated GO nanoflakes remained confined outside the cells (Figure S18, top), while for BNTPs the PGA coating played a role. In fact, noncoated BTNPs largely remained aggregated in clusters outside the cells, with a few ones internalized (Figure S18, bottom).…”
Section: Resultssupporting
confidence: 62%
“…More importantly, via a photobased mechanical tuning of the celladhesive micromaterials that can self-assembly with cells into 3D living composite microtissues, Kamperman et al recently reported an early onset elasticity-controlled lineage commit- ment of the differentiating stem cell spheroids. 108 As shown in Figure 5G, the visible-light-inspired postcuring of micromaterials yielded a well-defined and near-identical physiological stiffness in situ and led to a gradual and significant increase in adipogenesis and decrease in osteogenesis. In sum, these examples regarding to the impacts of light-tunable mechanical signaling all highlight the application potential of the photoresponsive hydrogels with an excellent adjustability in 3D culture.…”
Section: Acs Biomaterialsmentioning
confidence: 82%
“…32A). 170 The biotinyl group of the hydrogel enables stem cells to grow into microtissues through integrin binding, which provides a facile method to construct 3D cell spheroids. In addition to HRP, TGase has also demonstrated the ability to synthesize hydrogels, such as collagen gel 171 and PEG gel; 172 however, their application in living organisms is still rare.…”
Section: Covalent Strategies For Synthesizing Materials In Living Org...mentioning
confidence: 99%
“…Of note, the examples of enzymatic polymerization 160 (or biocatalytic polymerization 211 ) and oxidative polymerization 164 have expanded the scope and potential applications of in situ polymerization in living organisms. Moreover, crosslinking reactions triggered by enzymes, 170 light, 174 and chemical inducers 178 also enable the synthesis of intercellular or intracellular hydrogels to create stem cell spheroids, fix cells with maximum cellular complexity, and synthesize mimic RNA granules. Furthermore, bioconjugation reactions, such as modified Staudinger ligation 181 and click reaction, 183 also show the potential of introducing adducts to the cellular membrane for membrane engineering and tumor-targeted therapy.…”
Section: Future Trends and Perspectivesmentioning
confidence: 99%